Effect of Various Weed Management Practices on Weed Dynamics and Crop Yields under Maize-Wheat Cropping System of Western Hills - Acharya, Ramesh; Karki, Tika Bahadur; Adhikari, Bhawana (Agronomy Journal of Nepal, 2022)
Weeds pose a great challenge to cereal farmers and need to be managed before reaching the critical stage. An experiment was conducted to evaluate effect of various weed management practices on the weed dynamics and crop yields under the maize-wheat cropping system in 2019-2020 at research field of Directorate of Agricultural Research, Lumle, Kaski. The experiments consisted of six pre- emergence and post-emergence chemical management practices (Tembotrione post-emergence (PoE), Pendimethalin as pre-emergence (PE), Atrazine as (PoE), Atrazine as PE fb Tembotrione as PoE, Pendimethalin as PE fb 2,4-D Ethyl Ester (EE), Pendimethalin as PE fb Tembotrione as PoE for maize crop; Pendimethalin as PE, Pendimethalin as PE fb Manual weeding, Pendimethalin as PE fb Metribuzin, Pendimethalin as PE fb 2,4-D sodium salt as PoE, 2,4 D sodium salt as PoE, Metribuzin as PoE for wheat crop) compared with manual weeding and weedy check both maize and wheat. These treatments were studied in a randomized complete block design (RCBD) with three replications. Ageratum conyzoides and Chenopodium album were found to be the major weeds for the maize and wheat crop respectively. Atrazine as pre-emergence fb Tembotrione as post–emergence produced the highest yield (3.575 Mt ha-1) for maize season whereas 4.8 Mt ha-1 was obtained in Metribuzin treated plot as post emergence herbicide in wheat growing season. The yield increments by Tembotrione as post emergence was 71.51% and Metribuzin was 63.09% over weedy check. The findings could be useful for researchers and maize-wheat growing farmers of high rainfall ecologies.